Kajian Kepemimpinan Gaya Yesus Menjadi Pola Kepemimpinan Kristen - Like, Like (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
Jesus' style of leadership is very different from the leadership styles that this world teaches. Jesus' leadership style is one that can be found in the New Testament. To apply Jesus' leadership style to a Christian leadership pattern is not only proficient in theory and academically but requires an action and paradigm that is correct and a heart that is focused on God the Father and has an intimate relationship with God the Father. The purpose of this study was to describe the leadership style of Jesus in the form of servant leadership, pastor leadership, and management leadership. Studying the three styles (models) of Jesus' leadership styles will help Christian leaders to apply them to the correct Christian leadership pattern. The approach used in this research is the literature method with a descriptive qualitative approach.AbstrakKepemimpinan gaya Yesus sangat berbeda dengan gaya kepemimpinan yang dunia ini ajarkan. Gaya kepemimpinan Yesus adalah gaya yang dapat dijumpai di dalam Perjanjian Baru. Untuk menerapkan gaya kepemimpinan Yesus menjadi pola kepemimpinan Kristen bukan hanya mahir secara teori dan akademik namun membutuhkansuatu tindakan dan paradigma yang benar serta hati yang tertuju kepada Allah Bapa dan memiliki hubungan intim dengan Allah Bapa. Tujuan penelitian ini untuk mendeskripsikan kepemimpinan gaya Yesus berupa kepemimpinan hamba, kepemimpinan gembala, kepemimpinan pengurus. Mempelajari ketiga gaya (model) kepemimpinan gaya Yesus akan menolong pemimpin Kristen untuk menerapkannya menjadi pola kepemimpinan Kristen yang benar. Pendekatan yang digunakan